Environmental carbon capture service of the bofedales of the Upper Peru Town Center, Tacna - Sequeiros Abarca, Diego Abel (2020)
The evaluation of the environmental carbon capture service was carried out in the Centro Poblado Alto Peru, Tacna Region, from September to December 2019. Work began with collecting information from the study area, including downloading images from the Landsat 8 satellite, in order to calculate the Normalized Difference Vegetation Index (NDVI) and thus divide the study area according to the conservation status of plant cover. Subsequently, the samples were collected in the field, following the methodology of the World Agroforestry Centre (2009) collecting three types of samples referred to as; plant cover, peat/necromasse and organic soil in order to calculate the total organic carbon for each sample type. Finally, laboratory analyses were used for the determination of the carbon fraction and apparent density of the soil, the data of which were used for the total carbon stock. The results indicate that the total carbon is 157.18 Tn C/Ha, demonstrating the high potential of theofedales as a contribution to the environmental carbon capture service; and it is necessary to implement and strengthen conservation programmes.